Exploring the relationship between foreign language motivation and achievement among primary school students learning English in China. (April 2020) - Hu, Xiaoyi; McGeown, Sarah
Abstract: This study explored primary school students' foreign language (FL) motivation (expectancy-value) and its relationship with their FL achievement. In total, 631 Chinese primary school pupils (324 boys, 307 girls) aged between 9 and 12 years completed a questionnaire to report on their FL motivation (expectancy-value), and their teachers provided measures of their FL achievement in school. Students differentiated between expectancy and value components of motivation, and overall higher reports of value were found. While girls reported higher levels of FL motivation (particularly value), declines in students' FL motivation (expectancy and value) were found with increasing age. Results from regression analyses illustrated that both the expectancy and value components of motivation were significant independent predictors of students' FL achievement, accounting for approximately 40% of the variance. However, expectancy emerged as the stronger predictor across all ages and for both boys and girls. In light of these findings, pedagogical strategies such as shifting the emphasis from competitive to cooperative FL learning activities or providing students with more choice and autonomy over their FL activities can be adopted to enhance primary school students' FL motivation.